Facts and values in an historical investigation: dichotomy or interconnection? - Panafidina, Oksana; Mishalova, Olena (Actual Problems of Mind, 2017)
The paper deals with the problem of interrelation between facts and values in an historical investigation. The authors present an overview of the known approaches to this problem, and based on some methodological innovations of XX century defend the view about the interconnection of facts and values both on the factual and normative levels of an historical narrative.